1997
DOI: 10.1017/s0022215100139167
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the pathogenesis of radiation-induced injury to large arteries

Abstract: We report a case of a 35-year-old man who died of a brain infarct 20 months after radiotherapy for carcinoma of the tonsil with metastases to the cervical lymph nodes. Histology revealed mild atherosclerosis, necrotizing vasculitis, and occlusive thrombosis of the internal carotid artery. Significant changes were observed in the vasa vasorum: swelling and detachment of the endothelium, subendothelial oedema, hyaline change, fibrinoid necrosis of the vessel walls with mononuclear cellular infiltration, accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…Some authors have argued that chronic occlusive radiation vasculopathy is primarily an accelerated form of atherosclerosis 56,60 -63 ; others have described it as a distinct disease entity shaped by the initial radiation insult to the vasa vasorum. 15,59,64,65 Either way, it is the most radiosensitive mesenchymal cell common to both the artery proper and the vasa vasorum, the endothelial cell, 9 that bears the brunt of any XRT field effect. Fonkalsrud et al 55 used scanning electron microscopy to analyze the evolution of radiation vasculopathy in canine femoral arteries after a net dose of 40 Gray.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have argued that chronic occlusive radiation vasculopathy is primarily an accelerated form of atherosclerosis 56,60 -63 ; others have described it as a distinct disease entity shaped by the initial radiation insult to the vasa vasorum. 15,59,64,65 Either way, it is the most radiosensitive mesenchymal cell common to both the artery proper and the vasa vasorum, the endothelial cell, 9 that bears the brunt of any XRT field effect. Fonkalsrud et al 55 used scanning electron microscopy to analyze the evolution of radiation vasculopathy in canine femoral arteries after a net dose of 40 Gray.…”
Section: Pathogenesismentioning
confidence: 99%
“…It is this periadventitial scarring, often combined with advanced atheroma of the endothelium, that is most commonly described in surgical case series. 7,56,57,62 Documentation of disease evolution in the manner of Fonkalsrud et al 55 in humans is clearly impossible, but Zidar et al 59 described an autopsy case of a 35-year-old-man who succumbed to metastatic tonsillar carcinoma 20 months after XRT. Extensive focal inflammation and necrosis of the vasa vasorum and adventitium were seen.…”
Section: Pathogenesismentioning
confidence: 99%
“…4,10,11 The sequence of endothelial injury, cell detachment, thrombosis and fibrosis results in significant tissue injury that often limits radiation oncologist in attempting to deliver curative doses to a nearby tumor. The hallmark of radiation-induced injury is extensive fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Primary basic mechanisms behind radiation-induced cardiovascular disease appear to be endothelial dysfunction. [4][5][6] The sequence of endothelial injury, cell detachment, thrombosis and fibrosis results in significant tissue injury that often limits radiation oncologist in attempting to deliver curative doses to a nearby tumor. Fajardo and Steward have demonstrated that damage to the myocardium develops through three phases of injury.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, radiation-induced vascular injury is a well-known phenomenon, in which small arteries and capillaries are commonly and severely affected. Injuries of large arteries by radiation has been considered relatively rare, but the clinically important damage may be more common than previously thought [5,6]. This report describes 2 pediatric patients with moyamoya syndrome after radiation therapy: optic pathway glioma and medulloblastoma.…”
Section: Introductionmentioning
confidence: 96%